Laboratory Management in the Department of Office Governance Automation at SMK Nasional Makassar - Tiwi Tiwi; Risma Niswaty; Sirajuddin Saleh (ASHA Publishing, 2024)
Laboratories have an important role in education. The laboratory is a forum for students to develop themselves, as well as a place to practice a competency. Therefore, laboratory management must certainly be paid attention to. A laboratory with good conditions will facilitate the achievement of effective and efficient learning goals. This study aims to find out the management of the laboratory and to find out the inhibiting factors and supporting factors for the management of the office governance automation laboratory at the Makassar National Vocational High School. This research uses a qualitative approach with data collection techniques, namely observation, interviews, and documentation. The results of the study show that: 1) the planning carried out includes the planning of the laboratory use schedule, the planning of the procurement of equipment and equipment and the planning of the laboratory management officer which is carried out at the beginning of each semester. However, the planning for equipment procurement has not been fully realized due to budget limitations; 2) the organization of the office governance automation laboratory at the Makassar National Vocational High School has not taken place according to what has been made. This is evidenced by the lack of availability of laboratory management personnel; 3) Maintenance of the Office Governance Automation Laboratory at the Makassar National Vocational High School only carries out daily maintenance, for example sweeping and mopping the floor without regular maintenance. Thus, the maintenance of the office governance automation laboratory at the Makassar National Vocational High School has not been carried out optimally; and 4) supervision of the office governance automation laboratory at the Makassar National Vocational High School is only carried out preventively, namely preventing errors and damage to the use of the laboratory by applying discipline in the laboratory